Natural therapeutic approach of Nigella sativa (Black seed) fixed oil in management of Sinusitis - Mohaddese Mahboubi (Integrative Medicine Research)
Sinusitis is associated with inflammation and infections of air-filled cavities of sinuses. The aim of this study was to evaluate the potential efficacy of Nigella sativa seed fixed oil in management of sinusitis. The information was extracted from accessible international databases, traditional books, electronic resources, and unpublished data. Results: The results of investigations on N. sativa seed fixed oil showed its therapeutic potential in treatment of sinusitis by its anti-inflammatory, antioxidant, antihistaminic, immune-modulator, antimicrobial and analgesic effects. The use of N. sativa seed fixed oil can inhibit the inflammation of sinuses and respiratory airways, microbial infections and finally help the patients suffering from clinical symptoms of sinusitis such as coryza, nasal congestion, headache, neck pain, earache and toothache. Clinical studies are required to evaluate its efficacy in patients with sinusitis in future. Keywords: Nigella sativa seed fixed oil, Sinusitis, Nasal congestion, Pain, Inflammation